Overview of experiences of pregnant women about the role of nurses as educators on healthy behaviors of the Era of Sustainable Development Goals pregnancy - Much Nurkharistna Al Jihad; Sri Rejeki; Elis Hartati (Media Keperawatan Indonesia, 2020)
Maternal Mortality Rate (MMR) in Indonesia is still high. One of the indirect causes of maternal death is the behaviour of pregnant women. Information is needed about the role of nurses as educators on the healthy behaviour of pregnant women. The purpose of the study was to find a picture of the experience of pregnant women related to the role of nurses as educators on the healthy behaviour of pregnant women. This type of research is a qualitative phenomenological. As the population is pregnant women in the city of Semarang, samples were taken by convenience sampling technique of 6 people. Data collection was carried out by in-depth interviews. Analysis of qualitative data with the Colaizzi model. The results found 3 themes describing the role of nurses as educators on healthy behaviour of pregnant women, namely the role of nurses as educators, efforts made by pregnant women in pregnancy care, and expectation of mothers towards the role of nurses. The conclusion of this research is the role of nurses in healthy behaviour of pregnant women, healthy behaviour of mothers in the form of physical health care, nutritional needs of pregnant women, supporting food needs, routine examination of pregnant women (antenatal care), and establishing emotional relations with the fetus.